Innovative Physiotherapy Approaches in Managing Patellar Tendinopathy (Jumper’s Knee): An Updated Literature Review - Widanti, Herista Novia; Arti, Widi (Universitas Muhammadiyah Metro, 2024)
Introduction: Patellar tendinopathy (jumper's knee) is an overuse injury that usually has a gradual onset of pain. This condition is common in jumping athletes, characterized by local pain at the attachment of the proximal tendon to the bone and dysfunction of the patellar tendon during jumping and landing. Patellar tendinopathy clinically results from high loads on the tendon, such as jumping and changing direction. Patellar tendinopathy can affect health and quality of life by limiting participation in sports and activities for athletes. Objective: This study aims to summarize secondary data related to physiotherapy management of patellar tendinopathy. Methods: The research method used is a literature study using secondary data in the form of journals related to the topic of patellar tendinopathy (jumper's knee) obtained through Google Scholar, Science Direct, and PubMed. Results: From five recent journal articles obtained with various physiotherapy intervention protocols, the results were able to reduce symptoms in patients with patellar tendinopathy. Conclusion: Physiotherapeutic interventions such as progressive tendon-loading exercises (PTLE), Eccentric exercise programmes, Kinesio-tape® and isometric exercises are effective in reducing symptoms in patients with patellar tendinopathy. Keyword: patellar tendinopathy, jumper's knee, physiotherapy